Prevalent Risk Factors for Infectious Diseases in Children under 5 Years at a Tertiary Care Hospital in Karachi (Medical Forum Monthly, 2024)
Objective: Aim of the study was to determine the risk factors that leads to various infectious diseases (pneumonia, diarrhea, meningitis etc.) in young children at Civil Hospital Karachi. The study identifies the link between the infections and other factors like previous medical history, unhygienic conditions etc. and its impact on the health of under-five children.Study Design: Cross sectional study.Place and Duration of Study: This study was conducted at the Pediatrics Unit in Civil Hospital Karachi from March 2014 to August 2014.Materials and Methods: A sample size of 384 was achieved. Patients of aged 6 months to 5 years with infectious diseases were randomly selected and their mothers were asked questions related to it in a local language. Data was analyzed on SPSS version 16.Results: Pneumonia 115 (29.9%), Acute gastroenteritis 60 (15.6%) and meningitis/encephalitis 49 (12.7%) were most common diseases. 228 (59.4%) children were born premature, 234 (60.9%) had weight less than or equal to 2.5 kg. Only 74 (19.3%) of children were fully vaccinated. 239 (62.2%) had large family size with 222 (57.8%) claiming to have disease vectors present in their homes.Conclusion: Prematurity, low birth weight, non-vaccination and poor living conditions around child is linked with occurrence of infectious disease in children under 5 in our scenario.